Protective effect of soybean oil- or fish oil-rich diets on allergic airway inflammation - Navarro-Xavier, Roberta Araujo (J Inflamm Res, 2016)
BACKGROUND: The increased prevalence of asthma and allergic diseases in westernized societies has been associated with increased intake of diets rich in n-6 fatty acids (FAs) and poor in n-3 FAs. This study aimed to analyze the prophylactic effects of treatment with a soybean oil-rich diet (rich in n-6) or fish oil (rich in n-3) in an allergic airway inflammation model on lung inflammation score, leukocyte migration, T-helper cell (Th)-2 (interleukin [IL]-4, IL-5) and Th1 (interferon [IFN]-γ, tumor necrosis factor-α) cytokines, lipoxin A4, nitric oxide, bradykinin, and corticosterone levels in bronchoalveolar lavage (BAL) or lungs. METHODS: Male Wistar rats fed with soybean oil- or fish oil-rich diet or standard rat chow were sensitized twice with ovalbumin–alumen and challenged twice with ovalbumin aerosol. The BAL and lungs were examined 24 hours later. RESULTS: Both diets, rich in n-6 or n-3 FAs, impaired the allergic lung inflammation and reduced leukocyte migration, eosinophil and neutrophil percentages, and IL-4/IL-5/bradykinin levels in BAL and/or lungs, as well as increased the nitric oxide levels in BAL. The soybean oil-rich diet additionally increased the levels of lipoxin A4 and corticosterone in the lungs. CONCLUSION: Data presented demonstrated that the n-6 FA-rich diet had protective effect upon allergic airway inflammation and was as anti-inflammatory as the n-3 FA-rich diet, although through different mechanisms, suggesting that both diets could be considered as complementary therapy or a prophylactic alternative for allergic airway inflammation.